Leadership Theories: Application in the University Setting - Alajmi, Meaad (Technium Social Sciences Journal, 2022)
The paper discusses the application of three major theories of leadership in the education field. The paper starts with the trait theories and the possibility of its application in the education system from the highest position down to the teacher classroom. The second theory this paper sheds light on is the situational leadership theory. It looks into the literature regarding its application in the same system, i.e. education. The last theory this paper discusses is the contingency theory. It showcases the definition of the theory and the literature around its application in the educational system. The paper finally concludes that all theories are applicable according to the literature and research made on the topic.